2006
DOI: 10.1007/s11581-006-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Capacity fading of LiCr0.1Mn1.9O4/MPCF cells at elevated temperature

Abstract: Capacity fading of LiCr 0.1 Mn 1.9 O 4 /MPCF (mesophase pitch-based carbon fiber) cells was investigated at elevated temperature (55°C). The cells showed very fast capacity fading, keeping only 60% of capacity retention at the 100th cycle at 55°C. The cycled electrodes and the electrolyte were analyzed using electrochemical test, inductively coupled plasma, and X-ray diffraction. Results of the analyses indicated that LiCr 0.1 Mn 1.9 O 4 exhibited good effects on restraint of Mn dissolution and stabilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Doping is known to be an effective route. It is reported that substitution of Mn ions with other metals such as Li, Mg, Al, Cr, Co, Ni, Zn, Ga slows dissolution of Mn from the cathode into the electrolyte 15–27. Many researchers have reported that the introduction of cations with a low oxidation number increases the oxidation state of Mn ions.…”
Section: Introductionmentioning
confidence: 99%
“…Doping is known to be an effective route. It is reported that substitution of Mn ions with other metals such as Li, Mg, Al, Cr, Co, Ni, Zn, Ga slows dissolution of Mn from the cathode into the electrolyte 15–27. Many researchers have reported that the introduction of cations with a low oxidation number increases the oxidation state of Mn ions.…”
Section: Introductionmentioning
confidence: 99%